Locational analysis of quarries for the spatial planning of infrastructure: the case of the paved highway network of Veracruz State, Mexico - Martínez Santiago, Armando (2025)
The aim of the present work is to highlight the importance of territorial planning in the sustainable use of the raw material deposits located in the state of Veracruz, ranking first at the national level according to the National Inventory of Raw Material Deposits (NIRMD) 2011/2012 of the Secretariat of Communications and Transport (SCT). Raw material deposits are geological deposits of materials essential for the construction, maintenance and modernization of the basic infrastructure -communications and transport, electrical and hydraulic infrastructures-,social infrastructure–facilities to supply services and housing infrastructure-, and productive infrastructure –works aimed at the production and marketing of goods and services.